Hepatic cavernous hemangioma developed in non-small cell lung cancer patients after receiving Camrelizumab treatment: two case reports - Jin, Yonglong; Xu, Jinpeng; Zhuang, Dunmin; Dong, Lina; Sun, Yang; Zhao, Lin; Xiao, Wenjing (Frontiers in Oncology, 2023)
Purpose To report two cases of hepatic cavernous hemangioma, a rare complication, in patients with locally advanced and advanced non-squamous non-small cell lung cancer (NSCLC) treated with PD-1 inhibitors. Additionally, to share clinical experiences related to the management of this condition. Methods Two patients with locally advanced and advanced non-squamous non-small cell lung cancer (NSCLC) were enrolled in our hospital. Following the NCCN guidelines and expert consensus, both patients received standard treatment with Camrelizumab (PD-1 inhibitor). Subsequent abdominal CT scans revealed hepatic focal lesions that did not exhibit typical characteristics of metastatic tumors. Therefore, further systematic investigation was conducted to study the hepatic focal lesions. Results (1) Ultrasound-guided percutaneous biopsy confirmed the diagnosis of hepatic cavernous hemangioma. A multidisciplinary consultation concluded that it was an adverse drug reaction to Camrelizumab. (2) Ten-gene testing for both patients did not reveal any driver gene mutations associated with lung cancer. Apart from the occurrence of hepatic cavernous hemangioma, there were no signs of disease progression or worsening. (3) Both patients had resolution of hepatic cavernous hemangioma after switching to alternative PD-1 inhibitors or discontinuing PD-1 inhibitor treatment. One patient experienced hemorrhage related to the hepatic hemangioma, which was managed with hemostasis and symptomatic treatment, resulting in improvement. ( 4) Clinical outcomes: The first patient achieved a progression-free survival (PFS) of 33 months in first-line treatment and had not reached the PFS endpoint in second-line treatment, with an overall survival exceeding 56 months. The second patient had not reached the PFS endpoint in first-line treatment, with an overall survival exceeding 31 months. Conclusion Hepatic cavernous hemangioma is a rare and serious adverse reaction associated with PD-1 inhibitors. Camrelizumab may interact with the PD-1 molecule in a different manner compared to other PD-1 inhibitors, affecting the regulation of the VEGFR/ULBP2 signaling pathway. In future studies, next-generation sequencing may provide detailed molecular pathology information, which could help explain individual differences and provide a basis for the prevention or intervention of hepatic cavernous hemangioma.